Cameroon : Staff Report for the 2005 Article IV Consultation and Staff-Monitored Program. (IMF Staff Country Reports; Country Report ;, 2005)
Cameroon's 2005 Article IV Consultation reports that tangible progress has been made in the health and education sectors, and a number of social indicators have improved significantly. The deterioration in fiscal performance and related weaknesses in fiscal management could, in the longer term, threaten macroeconomic stability and debt sustainability. Moreover, sustainable private sector growth requires the authorities to address inadequate infrastructure, poor service delivery from troubled state enterprises, an investment climate overshadowed by poor governance and low levels of financial intermediation.